The Labor Market Effects of Restricting Refugees' Employment Opportunities - Achim Ahrens; Andreas Beerli; Dominik Hangartner; Selina Kurer; Michael Siegenthaler (Institute of Labor Economics (IZA), 2023)
Refugees, and immigrants more generally, often do not have access to all jobs in the labor market. We argue that restrictions on employment opportunities help explain why immigrants have lower employment and wages than native citizens. To test this hypothesis, we leverage refugees' exogenous geographic assignment in Switzerland, within-canton variation in labor market restrictions, and linked register data 1999–2016. We document large negative employment and earnings effects of banning refugees from working in the first months after arrival, from working in certain sectors and regions, and from prioritizing residents over refugees. Consistent with an effect of outside options on wages, removing 10% of jobs reduces refugees' hourly wages by 2.8% and increases the wage gap to similar host-country citizens in similar jobs by 2.2%. Furthermore, we show that restrictions reduce refugees' earnings even after they cease applying. Restrictions do not spur refugee emigration nor improve earnings of non-refugee immigrants.
Keywords: J08; J31; J42; J61; J68; 330; labor market integration; migration; labor market policies; labor market institutions; monopsony; refugees; employment; wages; outside options; employment opportunities